Effects of food and alcohol on the pharmacokinetics of an oral, extended-release formulation of hydrocodone in healthy volunteers - Farr SJ (Dove Medical Press, 2015)
Stephen J Farr,1 Cynthia Y Robinson,1 Christopher M Rubino2,3 1Zogenix, Inc., Emeryville, CA, 2Institute for Clinical Pharmacodynamics, Latham, NY, 3School of Pharmacy and Pharmaceutical Sciences, The State University of New York, University at Buffalo, Buffalo, NY, USA Background: The purpose of this study was to evaluate the pharmacokinetics, bioavailability, and safety of oral extended-release hydrocodone (HC-ER) when administered with food or alcohol. Methods: Two single-center, open-label, randomized, crossover studies were conducted in healthy volunteers. In a two-period food-interaction study, 12 subjects received HC-ER 20 mg after an overnight fast and a high-fat meal. In a three-period alcohol-interaction study, 30 naltrexone-blocked subjects received HC-ER 50 mg with a 0%, 20%, or 40% alcohol/orange juice solution after an overnight fast. Pharmacokinetic parameters were derived from plasma concentrations of hydrocodone and its metabolites. Results: Exposure to hydrocodone after HC-ER 20 mg was similar in the fed and fasted states, as assessed by area under the plasma concentration versus time curve from time of dosing to time of last detectable concentration (AUC0–t; 316.14 versus 311.94 ng · h/mL); relative bioavailability (Frel) was 101.74%. Differences (fed versus fasted) in hydrocodone mean maximum plasma concentration (Cmax; 28.86 versus 22.74 ng/mL) and median time to Cmax (tmax; 6 versus 8 hours) were not clinically significant. Administration of 20% alcohol with HC-ER 50 mg did not increase systemic exposure relative to 0% alcohol (AUC0–t 878 versus 832 ng · h/mL; Frel 105%) or result in clinically meaningful changes in Cmax (51.8 versus 46.3 ng/mL) or tmax (5.44 versus 6.16 hours). Administration with 40% alcohol increased AUC0–t (1,008 ng · h/mL versus 832 ng · h/mL; Frel 120%) and Cmax (109 versus 46.3 ng/mL), and shortened tmax (2.43 versus 6.16 hours). Adverse events occurred in 10.0%, 24.1%, and 66.7% of subjects after 0%, 20%, and 40% alcohol, respectively. Conclusion: HC-ER can be administered without regard to meals. While there was no evidence of "dose-dumping" (an unintended, rapid release in a short time period of all or most of the hydrocodone from HC-ER), even with 40% alcohol, as with all opioids, alcohol should not be ingested while using HC-ER. Keywords: opioid, food interaction, alcohol interaction, bioavailability, norhydrocodone, hydromorphone